Productivity of five pigeonpea (cajanus cajan) varieties in pigeonpea-maize strip intercroppin in Limpopo Province - Madimabe, Koketso Sherleen (My University, 2019)
Pigeonpea (Cajanus cajan (L) Millsp.) is an important grain legume crop in tropical and subtropical countries, where it provides a cheap source of protein. Smallholder farmers in Limpopo Province cultivate landraces of pigeonpea, which are characterised with late maturity, low grain yield and being sensitive to photoperiod. To increase the productivity of the cropping system involving pigeonpea, several earlymedium maturity varieties have been introduced. However, performance of the varieties has not been tested in strip intercropping in Limpopo Province. Farmers plant these landraces by using mixed intercropping without definite row arrangement. This practice does not optimise plant density; it hinders farm inputs application and is characterised producing low yields. Therefore, the inclusion of early maturing varieties of pigeonpea in an intercrop will enable farmers to select the best variety for planting in future and thus enhance their output as well as their productivity. The objectives of this study were to assess the agronomic performance of five pigeonpea varieties in pigeonpea-maize strip intercropping, to determine the effect of strip intercropping on maize yield and establish the effect of location and season variations on the performance of both component crops under the intercropping system. Experiments were conducted at the University of Limpopo Experimental Farm (UL Farm) and Ga-Thaba village during the 2015/16 and 2016/17 season. Five improved early-medium maturing pigeonpea varieties (ICEAP 001284, ICEAP 00604, ICEAP 87091, ICEAP 00661 and ICEAP 01101-2) from ICRISAT were evaluated under strip intercropping with maize cultivar PAN 6479. The varieties were selected as earlymedium maturing varieties from previous pigeonpea trials. The trials were laid in a split plot design. The main plot comprised cropping systems (intercrop and monocrop), while the subplot comprised the varieties with three replications. Data collected on pigeonpea were number of days to 50% flowering and 90% maturity number of primary branches; plant height (cm); number of pods per plant; pod length (cm); number of seed per pod; hundred seed weight (g); and grain yield (kg ha-1), whereas on maize, number of days to 50% tasselling and silking; plant height (cm); cob length (cm); cob per plant; grain yields (kg ha-1); and stover (kg ha-1) were recorded. LER was calculated to determine intercropping productivity. Data analysis was done using Statistic 10.0; and Least Significance Difference (LSD) was used to separate the means that showed significant differences at an alpha level of 0.05. The results revealed significant differences in nearly all pigeonpea variables expect (pod length, number of seed per pod and hundred seed weight). Variables that showed significant differences in maize were plant height, cob length, grain yields and stover. Number of days to 50% flowering and 90% physiological maturity differed significantly (P ≤ 0.05) among varieties at the UL Farm and Ga-Thaba. Varieties (ICEAP 001284 and ICEAP 00604) exhibited the shortest number of days to 50% flowering and 90% maturity in both locations during both seasons. The interaction between variety x season (V x S) showed significant (P ≤ 0.05) differences in pigeonpea grain yield. The top yielders during 2015/16 at the UL Farm were ICEAP 01101-2 (1555 kg ha-1) and ICEAP 001284 (1280 kg ha-1), while during the 2016/17 season, they were ICEAP 001284 (937 kg ha-1) and ICEAP 01101-2 (912 kg ha-1). High yielder at Ga-Thaba during the 2016/17 season were ICEAP 001284 and ICEAP 01101-2 with grain yields of 671 kg ha-1 and 627 kg ha-1, respectively. Furthermore, varieties that obtained high yields during the 2015/16 season were ICEAP 001284 (504 kg ha-1) and ICEAP 00604 (541 kg ha-1). Most of the varieties during both seasons at the UL Farm and Ga-Thaba yielded more than 500 kg ha-1 under strip intercropping as compared to mixed intercropping, which obtained yields averages of below 400 kg ha-1. The highest maize grain yields of 1450 kg ha-1 were recorded during 2015/16 as compared to 958 kg ha1 during the 2016/17 season at the UL Farm. The calculated total Land Equivalent Ratio (LER) for the two crops in both locations gave positive and higher than 1 values, which suggests a favourable grain yield advantage for maize-pigeonpea strip intercrop over mixed intercropping. Key words: Cajanus cajan, maize, cropping system, maturity, grain yields, land equivalent ratio
Thesis (M. Sc. Agriculture (Agronomy)) -- University of Limpopo, 2019
Keywords: Cajanus cajan; Maize; Cropping system; Maturity; Grain yields; Lland equivalent ratio; Pigeon pea; Hedgerow intercropping